Intellectual property rights and the competitiveness of academic spin-offs - Aurora Amélia Castro Teixeira; Cátia Ferreira (Journal of Innovation & Knowledge (JIK), 2019)
Very few quantitative studies assess the impact of IPR protection mechanisms on the competitiveness of companies, particularly those whose creation and existence is often attributed to high technology/knowledge intensity. The present study aims to fill this gap. Through a direct survey targeting startups located in S&T parks and incubators, we assess the direct and indirect impact of IPR protection mechanisms. Logistics estimations based on a sample of 48 Portuguese companies suggest that, considered globally, formal IPR protection is detrimental to the companies' competitiveness. Notwithstanding, when IPR protection mechanisms are discriminated by type, the results indicate that the use of informal protection mechanisms, such as lead time and trade secrets, fosters the companies' competitiveness, whereas the use of formal protection mechanisms, in particular, patents, trademarks and geographical indications, negatively impacts on competitiveness. The size and innovation profile of the company intermediates the influence of IPR protection on its competitiveness.
Keywords: 650; Academic spin-offs (ASOs); Competitiveness; Intellectual property rights (IPRs); Science and technology (S&T) parks and incubators; Startups